2022
DOI: 10.1089/tmj.2021.0102
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Level Factors Associated with Utilization of Telemedicine Services from a Free Clinic During COVID-19

Abstract: Background: Disparities in telemedicine use by race, age, and income have been consistently documented. To date, research has focused on telemedicine use among patients with adequate insurance coverage. To address this gap, this study identifies patient-level factors associated with telemedicine use during the coronavirus (COVID-19) pandemic among one free clinic network's patients who are underinsured or uninsured. Materials and Methods: Electronic health record data were reviewed for patient-level data on pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
3
13
2
1
Order By: Relevance
“…Our data indicated there was no difference in the likelihood to return to clinic based on race or ethnicity. This is consistent with other studies which showed no racial or ethnic disparities with telehealth utilization [22,28,29]. Lack of access to healthcare has become increasingly relevant as millions of individuals have recently lost health insurance because of pandemic-related unemployment [30].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our data indicated there was no difference in the likelihood to return to clinic based on race or ethnicity. This is consistent with other studies which showed no racial or ethnic disparities with telehealth utilization [22,28,29]. Lack of access to healthcare has become increasingly relevant as millions of individuals have recently lost health insurance because of pandemic-related unemployment [30].…”
Section: Discussionsupporting
confidence: 91%
“…Older patients (≥ 45 years old) were more likely to return to clinic than younger patients (< 45 years old) after the onset of the COVID-19 pandemic. We know that there exists a generational technological divide between older and younger patients in that older patients are less likely to access the internet, use smartphones and have digital literacy [22,[24][25][26]. Therefore, this finding was somewhat surprising as our clinic had switched to telehealth-only available appointments in March 2021 and older patients were thought to be less likely to utilize technology, including telehealth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, established patients were more likely to complete telehealth appointments, a finding consistent with other studies demonstrating that—among diverse patient populations during the pandemic—new patients were less likely to use the technology 6 . There was no policy barring new patients from being seen in person; variation in new patient appointments may have depended on acuity and whether laboratory or imaging studies were needed.…”
Section: Discussionsupporting
confidence: 87%
“…The early phase of the pandemic was associated with reduced in-person pediatric visits 4 . Accordingly, telehealth strategies could generate new opportunities to overcome, or exacerbate, longstanding obstacles to care provision for medically and socially marginalized populations 5 , 6 , 7 . Both federal and state programs seek to expand infrastructure technologies in support of telehealth.…”
Section: Introductionmentioning
confidence: 99%